The prognostic value of boost dose in residual cervical lymph nodes in nasopharyngeal carcinoma patients after intensity-modulated radiotherapy: a retrospective study - Mengting Xu; Liuling Wang; Jianming Ding; Yiying Xu; Zhaodong Fei (BMC Cancer)
Abstract Background The administration of a boost dose to residual cervical lymph nodes (RCLN) following radiotherapy for nasopharyngeal carcinoma (NPC) remains a controversial contentious issue. This study explored the prognosis of NPC patients with such residuals and evaluated the impact of an intensity-modulated radiotherapy (IMRT) boost on outcome. Methods Two thousand six hundred thirty-three NPC patients following radical IMRT were retrospectively conducted. Clinical data of 1057 NPC patients with RCLN after radical IMRT were analyzed and 199 patients received boost radiation. To balance possible confounders between groups, propensity score matching (PSM) was carried out (ratio: 1:2). Risk classification was according to postradiotherapy Epstein-Barr virus (EBV) DNA and N category. Results Patients with positive RCLN findings exhibited considerably lower 3-year relapse-free survival (RRFS), overall survival (OS), progression-free survival (PFS), and distant metastasis-free survival (DMFS) rates compared to those with negative findings (98.0% vs. 92.8%; 93.5% vs. 85.0%; 87.0% vs. 68.4%; 92.8% vs. 81.9%, all P < 0.001). Multivariate analysis indicated that N category and postradiotherapy EBV DNA levels as high-risk factors for RCLN. In the matched cohort, the boost radiation group showed improved 3-year OS (89.4% vs. 80.0%, P < 0.001), RRFS (95.0% vs. 89.8%, P = 0.019), PFS (73.8% vs. 63.7%, P = 0.004), and DMFS (85.2% vs. 74.2%, P = 0.001). Multivariate analysis confirmed boost radiation as a critical protective prognostic factor. Conclusion For NPC patients with RCLN, adding a boost dosage following radical IMRT results in desirable tumor control and a positive clinical outcome. Individuals with detectable EBV DNA and N2-3 category may benefit from the boost radiation.